Prochlorococcus and Synechococcus have Evolved Different Adaptive Mechanisms to Cope with Light and UV Stress - Mella-Flores, Daniella; Six, Christophe; Ratin, Morgane; Partensky, Frédéric; Boutte, Christophe; Le Corguillé, Gildas; Blot, Nicolas; Gourvil, Priscillia; Kolowrat, Christian; Garczarek, Laurence; Marie, Dominique (Frontiers in Microbiology, 2012)
Prochlorococcus and Synechococcus, which numerically dominate vast oceanic areas, are the two most abundant oxygenic phototrophs on Earth. Although they require solar energy for photosynthesis, excess light and associated high UV radiations can induce high levels of oxidative stress that may have deleterious effects on their growth and productivity. Here, we compared the photophysiologies of the model strains Prochlorococcus marinus PCC 9511 and Synechococcus sp. WH7803 grown under a bell-shaped light/dark cycle of high visible light supplemented or not with UV. Prochlorococcus exhibited a higher sensitivity to photoinactivation than Synechococcus under both conditions, as shown by a larger drop of photosystem II (PSII) quantum yield at noon and different diel patterns of the D1 protein pool. In the presence of UV, the PSII repair rate was significantly depressed at noon in Prochlorococcus compared to Synechococcus. Additionally, Prochlorococcus was more sensitive than Synechococcus to oxidative stress, as shown by the different degrees of PSII photoinactivation after addition of hydrogen peroxide. A transcriptional analysis also revealed dramatic discrepancies between the two organisms in the diel expression patterns of several genes involved notably in the biosynthesis and/or repair of photosystems, light-harvesting complexes, CO2 fixation as well as protection mechanisms against light, UV and oxidative stress, which likely translate profound differences in their light-controlled regulation. Altogether our results suggest that while Synechococcus has developed efficient ways to cope with light and UV stress, Prochlorococcus cells seemingly survive stressful hours of the day by launching a minimal set of protection mechanisms and by temporarily bringing down several key metabolic processes. This study provides unprecedented insights into understanding the distinct depth distributions and dynamics of these two picocyanobacteria in the field.